Attitudes of EFL Learners in Kuwait Toward Project-Based Approach - Alobaidan, Aishah Sami (European Scientific Journal, ESJ, 2025)
Investigating learners’ attitudes is highly relevant to the improvement of teaching strategies and educational outcomes. The current study attempts to examine the attitudes of female EFL learners in the College of Basic Education in Kuwait toward the integration of project-based learning (PBL) in their English courses. The data were collected quantitatively using a questionnaire designed for the purpose of the study. The participants completed the questionnaire after experiencing PBL for about two months in their compulsory general English courses. The results revealed clear positive attitudes of these learners toward this student-centered method. The participants of the study have reported improvements in their English language skills, self-confidence, motivation, collaborative skills, and planning. These results can be used to improve the quality of English teaching in Kuwait and encourage the integration of PBL in all English classes in Kuwait’s public educational institutions. It is hoped that by encouraging the adoption of these modern strategies, Kuwait can enhance 21st-century skills among the graduates of its institutions and prepare them to be active and productive in their future careers.